The Importance of Creative Tasks in Physics Lessons - Brice, Tamāra; Brice, Inga (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Pupils should be more involved in their own education, allowed to ask questions, to express their own views and to creatively think and create. The creative process is essential for motivation based on interest, pleasure and a challenge gained in the process. To develop these skills alongside the theory and exercises practical research tasks and other creative activities have been introduced in Physics to the pupils of 8th grade. As pupils from interest in the subject they will want to participate, and the next task will probably involve more children. In order to encourage students to think in physics lessons and work creatively, propose them to make their own musical instruments, allow to prepare their own ideas and initiatives such as the shadow theater in the form of fairy tales, choose the number comprehensible experiments.